Pengaruh Media Monopoli Kata Berbasis Boardgame Terhadap Kemampuan Literasi dan Numerasi Ditinjau dari Perbedaan Gender Siswa - Dyahpuspita, Nurrina; Kuntoro, Kuntoro (Jurnal Didaktika Pendidikan Dasar, 2025)
Literacy and Numeracy skills are the ability to identify, understand, interpret, create, communicate and calculate, using printed and written materials related to various contexts. This research aims to determine the effect of Boardgame Monopoli Kata media on literacy and numeracy skills in grade I students at SDN 1 Bancarkembar. The research method uses an experimental factorial design developed by Fraenkel. The research subjects were 40 students using nonprobability sampling techniques. Data collection is carried out through observation, tests, and documentation. The data analysis technique uses two- way analysis of variance (ANOVA). The results of the research show that: 1) Boardgame Monopoli Kata media has an effect on the experimental group, 2) There is no interaction between learning media and gender differences on students’ literacy and numeracy abilities, 3) Boardgame Monopoli Kata media has an effect on participants’ literacy and numeracy abilities as male students, 4) Boardgame Monopoli Kata Media has an effect on the literacy and numeracy skills of female students.